SEASONAL VARIATION OF THE PHYSICO-CHEMISTRY QUALITY OF A TRIBUTARY OF THE BONNY ESTUARY, RIVERS STATE, NIGERIA - Davies, Onome Augustina (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
Okpoka Creek is a tributary of the Upper Bonny Estuary in the Niger Delta, Nigeria. The study evaluated the effects of season (wet and dry) on the physico-chemical characteristics of this creek. Surface water samples were collected monthly from May 2004 April 2006 to cover two seasons according to standard methods. Turbidity, 2.31 ±0.14 NTU (dry) and 4.68 ±0.55 NTU (wet) and temperature, 28.38 ± 0.09oC (wet) and 28.94±0.08oC (dry) showed significant seasonal variations (P<0.001). Dry season dissolved oxygen (5.14 ±0.16 mg/L) and biological oxygen demand (3.43±0.15 mg/L) were significantly higher than wet season values (4.80 ± 0.14 mg/L and 3.11±0.12 mg/L respectively)(P<0.05). Wet season total organic carbon (TOC) (114.16±4.39 mg/L) and total organic matter (TOM) (207.46±7.32 mg/L) significantly exceeded that of dry season (89.26±4.26 mg/L and 153.27±7.35 mg/L respectively) (P<0.05). TOC values at both seasons were above 1 to 30 mg/L for natural aquatic environment. Phosphate and ammonia exceeded FEPA and USEPA acceptable levels of 0.10 mg/L each for natural water bodies. Nitrate, phosphate and sulphate had significant seasonal variations (P<0.05). The presence of high levels of TOC and phosphate especially at wet season indicates organic pollution and stress. Run-offs from the creek environs, increasing inflow of water from Bonny Estuary and anthropogenic wastes especially dredged materials, slaughter effluents and raw human faeces lead to high organic loads at wet season. The study therefore suggests concerted environmental surveillance on Upper Bonny Estuary to reduce the inflow of pollutants from Bonny Estuary and anthropogenic sources into this creek especially at wet season.